Transforming food systems with trees and forests. Issue 7 (July 2022) - Ickowitz, Amy; McMullin, Stepha; Rosenstock, Todd; Dawson, Ian; Rowland, Dominic; Powell, Bronwen; Mausch, Kai; Djoudi, Houria; Sunderland, Terry; Nurhasan, Mulia; Novak, Andreea; Gitz, Vincent; et al.
Summary: The global food system is failing to deliver sufficient and nutritious food to all, while damaging the earth and unsustainably drawing down its resources. We argue that trees and forests are essential to solving these challenges. We outline the current contributions of trees and forests to the global food system and present recommendations to leverage these contributions as part of the efforts to reshape food systems to better support healthy diets and environmental sustainability. Trees and forests provide nutrient-rich foods, incomes for food security, ecosystem services for food production, and add resilience to food systems. At the same time, trees and forests protect biodiversity and mitigate climate change through carbon sequestration. We recommend four approaches to realise the full potential of trees and forests to contribute to healthy and sustainable food systems: scaling up current tree-based food production, reorientating some agricultural investments towards nutrient-dense food production, repurposing production incentives from support of calorie-rich but nutrient-poor foods to support nutrient-dense foods, and integrate nutrition objectives into forest conservation and restoration programmes. Trees and forests have important roles to play in the transformation of our food systems, but more needs to be done to ensure that these roles are realised.